2016
DOI: 10.1534/genetics.115.186270
|View full text |Cite
|
Sign up to set email alerts
|

Host Mitochondrial Association Evolved in the Human ParasiteToxoplasma gondiivia Neofunctionalization of a Gene Duplicate

Abstract: In Toxoplasma gondii, an intracellular parasite of humans and other animals, host mitochondrial association (HMA) is driven by a gene family that encodes multiple mitochondrial association factor 1 (MAF1) proteins. However, the importance of MAF1 gene duplication in the evolution of HMA is not understood, nor is the impact of HMA on parasite biology. Here we used within- and between-species comparative analysis to determine that the MAF1 locus is duplicated in T. gondii and its nearest extant relative Hammondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 56 publications
3
71
0
Order By: Relevance
“…With the exception of ASP5, and as might be expected, all proteins so far published to be required for effector translocation across the PVM localize to the PV/PVM (2). Of the 10 proteins chosen for further analysis, GRA44, GRA45, CST1, GRA7, GRA52, and MAF1a are all known to be PV/PVM localized (26,(30)(31)(32)(33)(34)(35)(36)(37). The localization of 211460 and PPM3C has not been reported, but both include predicted signal peptides (see below), as does 204340, which has been described to possibly be micronemal (34).…”
Section: Resultsmentioning
confidence: 79%
“…With the exception of ASP5, and as might be expected, all proteins so far published to be required for effector translocation across the PVM localize to the PV/PVM (2). Of the 10 proteins chosen for further analysis, GRA44, GRA45, CST1, GRA7, GRA52, and MAF1a are all known to be PV/PVM localized (26,(30)(31)(32)(33)(34)(35)(36)(37). The localization of 211460 and PPM3C has not been reported, but both include predicted signal peptides (see below), as does 204340, which has been described to possibly be micronemal (34).…”
Section: Resultsmentioning
confidence: 79%
“…These include dose, parasite stage, initiating infection, parasite genotype, host genotype, and various factors that affect the host's immune status, especially interaction of, and concomitant infection with other pathogens 7 . In eukaryotic parasites like Toxoplasma gondii, virulent alleles at multiple locations in the genome determine the pathogenicity 8 . Overall, the geographic origin of the patients influence the presence of different T. gondii strains; however, virulent strains containing type I, or atypical alleles are known to be more pathogenic or more likely to cause severe diseases in patients.…”
Section: Dear Editormentioning
confidence: 99%
“…Previous work has established that expression of a host mitochondrial association-competent (HMA + ) copy of the T. gondii protein, mitochondrial association factor 1 (MAF1b), alters the host cytokine response ( 12 ) and provides a competitive advantage during the acute phase of infection in a mouse model ( 13 ). At 5 days postinfection (dpi), the serum concentrations of 14 out of 26 cytokines tested (interleukin-10 [IL-10], granulocyte colony-stimulating factor [G-CSF], IL-3, IL-1a, Ccl5, Ccl7, IL-13, IL-4, IL-23, IL-2, IL12p70, interferon gamma [IFN-γ], IL-6, and Ccl3) were reduced in mice infected with a T. gondii RHΔMAF1 mutant compared to mice infected with the wild-type strain (RH:WT) ( 12 ), although there were no significant MAF1-dependent differences in mouse morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…At 5 days postinfection (dpi), the serum concentrations of 14 out of 26 cytokines tested (interleukin-10 [IL-10], granulocyte colony-stimulating factor [G-CSF], IL-3, IL-1a, Ccl5, Ccl7, IL-13, IL-4, IL-23, IL-2, IL12p70, interferon gamma [IFN-γ], IL-6, and Ccl3) were reduced in mice infected with a T. gondii RHΔMAF1 mutant compared to mice infected with the wild-type strain (RH:WT) ( 12 ), although there were no significant MAF1-dependent differences in mouse morbidity. However, it has also been shown that expression of an HMA + copy of MAF1 (specifically TgMAF1RHb1 [ 13 ; GenBank accession no. KU761334 ], here referred to as MAF1b) in parasites that do not normally exhibit HMA provided a competitive advantage in a mixed population of HMA + and HMA − parasites during the acute phase of infection ( 13 ), suggesting that in the type II genetic, background, MAF1b expression (and therefore HMA itself) can influence infection outcome in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation